2022
DOI: 10.3389/fphys.2022.840722
|View full text |Cite
|
Sign up to set email alerts
|

Post-Activation Performance Enhancement: Save Time With Active Intra-Complex Recovery Intervals

Abstract: This study aimed to determine whether the intra-complex active recovery within the strength-power potentiating complex will impact the upper-body post-activation performance enhancement effect and how the magnitude of this effect will change across the upper-body complex training session. Thirteen resistance-trained males [the age, body mass, height, experience in resistance training, and one-repetition maximum (1RM) in bench press were 27 ± 4 years; 92.3 ± 15.4 kg; 182 ± 6 cm; 6.4 ± 2.4 years, and 118 ± 29 kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 28 publications
(53 reference statements)
0
6
0
Order By: Relevance
“…Along the same lines, Urbański et al (2023) demonstrated that the completion of an active ICRI (i.e., bench press exercise at 75% of 1RM) did not significantly impact lower-body PAPE responses (i.e., in contrast pairs consisting of a back squat and a hip thrust paired with a CMJ and a broad jump, respectively) in comparison with a condition in which participants rested seated. Thus, to some extent, previous literature ( Trybulski et al, 2022 ; Urbański et al, 2023 ) supports the current findings in the sense that matching neuromuscular performances were found when completing a task during the ICRI or when simply allowing a passive recovery between exercises. However, direct comparisons should be made with caution since: 1) Trybulski et al (2022) investigated upper-body contrast pairs (as opposed to lower-body in the present investigation); and 2) both mentioned studies ( Trybulski et al, 2022 ; Urbański et al, 2023 ) prescribed ICRIs considerably longer than those used here (i.e., ~6 min vs. 2 min 30 s), which may limit their application in time-constrained scenarios (e.g., team-sport settings).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Along the same lines, Urbański et al (2023) demonstrated that the completion of an active ICRI (i.e., bench press exercise at 75% of 1RM) did not significantly impact lower-body PAPE responses (i.e., in contrast pairs consisting of a back squat and a hip thrust paired with a CMJ and a broad jump, respectively) in comparison with a condition in which participants rested seated. Thus, to some extent, previous literature ( Trybulski et al, 2022 ; Urbański et al, 2023 ) supports the current findings in the sense that matching neuromuscular performances were found when completing a task during the ICRI or when simply allowing a passive recovery between exercises. However, direct comparisons should be made with caution since: 1) Trybulski et al (2022) investigated upper-body contrast pairs (as opposed to lower-body in the present investigation); and 2) both mentioned studies ( Trybulski et al, 2022 ; Urbański et al, 2023 ) prescribed ICRIs considerably longer than those used here (i.e., ~6 min vs. 2 min 30 s), which may limit their application in time-constrained scenarios (e.g., team-sport settings).…”
Section: Discussionsupporting
confidence: 89%
“…However, evidence is scarce regarding the effects of including another CA or a mobility exercise during ICRIs. Trybulski et al (2022) evaluated the acute effects of incorporating a low-intensity exercise (i.e., a Swiss ball leg curl) within an upper-body strength-power potentiating complex (i.e., bench press + BPT) when compared to a passive ICRI. Those authors found similar PAPE responses in both conditions and concluded that performing body-weighted auxiliary exercises during the ICRI could be a viable option to optimize the CCT prescription from a time-efficiency perspective ( Trybulski et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the effective ways to increase an upward and rightward force-velocity relationship is the use of a loaded conditioning activity (CA) before a power exercise to evoke acute post-activation performance enhancement (PAPE) ( Blazevich and Babault, 2019 ; Blecharz et al, 2022 ; Cormier et al, 2022 ; Trybulski et al, 2022 ; Wolska et al, 2023 ) or increased competition performance ( Bogdanis et al, 2014 ; Chua et al, 2021 ). Some general mechanisms such as changes in muscle temperature, cellular water content, muscle activation, alterations in the motor pattern, and post-activation potentiation effect have been identified as PAPE causes ( Blazevich and Babault, 2019 ; Xenofondos et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%